Trait interactions effects on tropical tree demography depend on the environmental context - Kamimura, Vitor de A.; Loiola, Priscilla de P.; Carmona, Carlos P.; Assis, Marco A.; Joly, Carlos A.; Santos, Flavio A.M.; Vieira, Simone A.; Alves, Luciana F.; Martins, Valéria F.; Ramos, Eliana; Ramos, Rafael F.; de Bello, Francesco (Perspectives in plant ecology, evolution and systematics, 2023)
Although functional traits are defined based on their impact on demographic parameters, trait-demography relationships are often reported as weak. These weak relationships might be due to disregarding trait interactions and environmental contexts, which should modulate species trait-demography relationships. We applied different models, including boosted regression tree (BRT) models, to investigate changes in the relationship between traits and demographic rates of tropical tree species in plots along an elevational gradient and among time intervals between censuses, analyzing the effect of a strong drought event. Based on a large dataset of 18,000 tree individuals from 133 common species, distributed among twelve 1-ha plots (habitats) in the Atlantic Forest (Brazil), we evaluated how trait interactions and the environmental context influence the demographic rates (growth, mortality, and recruitment). Functional traits, trait-trait, and trait-habitat interactions predicted demography with a good fit through either BRTs or linear mixed-models. Changes in growth rates were best related to size (diameter), and mortality rates to habitats, while changes in recruitment rates were best related to the specific leaf area. Moreover, the influence of traits differed among time intervals, and for demographic parameters, habitat affected growth and mortality by interacting with diameter. Here, we provide evidence that trait-demography relationships can be improved when considering the environmental context (space and time) and trait interactions to cope with the complexity of changes in the demography of tropical tree communities. Thus, to expand predictions of demography based on functional traits, we show that it is useful to fully incorporate the concept of multiple trait-fitness optima, resulting from trait interactions in different habitats and growth conditions. •We explored trait-demography relationships of tree species along an elevational gradient.•Trait-demography relationships can vary along environmental gradients.•Assessing the combined effect of multiple traits is important to expand demography predictions based on traits.•The ‘functionality’ of traits can be evaluated by using statistical techniques that consider interactions between traits and between traits and the environment.